Efektifitas Model Pembelajaran Problem Solving berbantuan Media Belajar Pabala terhadap Kemampuan Pemecahan Masalah Siswa - Catur Singgih; Zulmi Roestika Rini (JANACITTA, 2025)
Abstract This research aims to evaluate the effectiveness of the problem-solving learning model assisted by the Pabala learning media in improving problem-solving skills among third-grade students at MI Gedanganak. The main issue identified is the low problem-solving abilities among students. This research uses a quantitative approach, with the population consisting of all students at MI Gedanganak, and the sample taken from class IIIB with 26 students as the experimental group and class IIIC with 26 students as the control group. Data were collected through testing techniques, namely pretest and posttest, as well as non-testing techniques, including observation, questionnaires, and documentation. Data analysis was conducted using various statistical tests, including normality tests, homogeneity tests, regression tests, independent sample t-tests, and paired sample t-tests. The research findings indicate that: (1) there is a significant effect of the problem-solving learning model assisted by Pabala learning media on improving problem-solving skills, with a significance level of 0.000 < 0.05; (2) there is a significant difference in problem-solving abilities between students in the experimental and control classes, with a significance level of 0.014 < 0.05; (3) this learning model effectively enhances students' problem-solving skills, evidenced by a significance level of 0.000 < 0.05. In conclusion, the problem-solving learning model assisted by Pabala learning media is proven effective in improving students' problem-solving abilities. Abstrak Penelitian ini bertujuan untuk mengevaluasi keefektifan model pembelajaran problem solving dengan media belajar Pabala dalam meningkatkan kemampuan pemecahan masalah siswa kelas III MI Gedanganak. Masalah utama yang diidentifikasi adalah rendahnya kemampuan pemecahan masalah di kalangan siswa. Penelitian ini menggunakan pendekatan kuantitatif, dengan populasi seluruh siswa di MI Gedanganak dan sampel diambil dari kelas IIIB sebanyak 26 siswa sebagai kelompok eksperimen dan kelas IIIC sebanyak 26 siswa sebagai kelompok kontrol. Data dikumpulkan melalui teknik tes yaitu pretest dan posttest serta teknik non tes yaitu observasi, kuesioner dan dokumentasi. Analisis data dilakukan melalui beberapa uji statistik, seperti uji normalitas, homogenitas, regresi, independent sample t-test, dan paired sample t-test. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh signifikan dari penggunaan model pembelajaran problem solving berbantuan media Pabala terhadap peningkatan kemampuan pemecahan masalah, dengan taraf signifikansi 0,000 < 0,05; (2) terdapat perbedaan signifikan antara kemampuan pemecahan masalah siswa di kelas eksperimen dan kontrol, dengan taraf signifikansi 0,014 < 0,05; (3) model pembelajaran ini secara efektif meningkatkan kemampuan pemecahan masalah siswa, terbukti dengan taraf signifikansi 0,000 < 0,05. Kesimpulannya, model pembelajaran problem solving berbantuan media belajar Pabala terbukti efektif dalam meningkatkan kemampuan pemecahan masalah siswa.